Taking the Reins on Systems of Care for ST-Segment–Elevation Myocardial Infarction Patients: A Report From the American Heart Association Mission. (May 2018) - Green, Jacqueline L.; Jacobs, Alice K.; Holmes, DaJuanicia; Chiswell, Karen; Blanco, Rosalia; Bates, Eric R.; French, William; Kupas, Douglas F.; Mears, Greg; Roe, Matthew; Nallamothu, Brahmajee K.
Abstract : Background—: Early success with regionalization of ST-segment–elevation myocardial infarction (STEMI) care has led many states to adopt statewide prehospital STEMI hospital destination policies, allowing emergency medical services to bypass non–percutaneous coronary intervention–capable hospitals. The association between adoption of these policies and patterns of care among STEMI patients is unknown. Methods and Results—: Using data from January 1, 2013, to December 31, 2014, from the National Cardiovascular Data Registry and Acute Coronary Treatment and Intervention Outcomes Network Registry, 6 states with bypass policies (cases included Delaware, Iowa, Maryland, North Carolina, Pennsylvania, and Massachusetts) were matched to 6 states without bypass policies (controls included South Carolina, Minnesota, Virginia, Texas, New York, and Connecticut) a priori on region, hospital density, and percent state participation in the registry. Using the matched sample, logistic regression models were adjusted for patient- and state-level characteristics. Outcomes were receipt of reperfusion and receipt of timely percutaneous coronary intervention. Our study cohort included 19 287 patients at 379 sites across 12 states. Patients from states with hospital destination policies were similar in age, sex, and comorbidities to patients from states without such policies. After adjustment for patient- and state-level characteristics, 57.9% (95% confidence intervals, 53.2%–62.5%) of patients living in states with hospital destination policies when compared with 47.5% (95% confidence intervals, 43.4%–51.7%) living in states without hospital destination policies received primary percutaneous coronary intervention within their relevant guideline-recommended time from first medical contact. Conclusions—: Statewide adoption of STEMI hospital destination policies allowing emergency medical services to bypass non–percutaneous coronary intervention–capable facilities is associated with significantly faster treatment times for patients with STEMI.